Pricing in road transport a multi-disciplinary perspective - Verhoef, Erik T. (Edward Elgar, 2008)
Transport pricing is high on the political agenda throughout the world, but as the authors illustrate, governments seeking to implement this often face challenging questions and significant barriers. The associated policy and research questions cannot always be addressed adequately from a mono-disciplinary perspective. This book shows how a multi-disciplinary approach may lead to new types of analysis and insights, contributing to a better understanding of the intricacies of transport pricing and eventually to a potentially more effective and acceptable design of such policies. The study addresses important policy and research themes such as the possible motives for introducing road transport pricing and potential conflicts between these motives, behavioural responses to transport pricing for households and firms, the modelling of transport pricing, and the acceptability of pricing
Includes bibliographical references and index
Keywords: Straßenbenutzungsgebühr; User charges; Congestion pricing; Toll roads; Aufsatzsammlung